Live or death in cells: from micronutrition metabolism to cell fate - Wang, Yuting; Wu, Wei; Gong, Jianke (Frontiers in Cell and Developmental Biology, 2023)
Micronutrients and cell death have a strong relationship and both are essential for human to maintain good body health. Dysregulation of any micronutrients causes metabolic or chronic diseases, including obesity, cardiometabolic condition, neurodegeneration, and cancer. The nematode Caenorhabditis elegans is an ideal genetic organism for researching the mechanisms of micronutrients in metabolism, healthspan, and lifespan. For example, C. elegans is a haem auxotroph, and the research of this special haem trafficking pathway contributes important reference to mammal study. Also, C. elegans characteristics including anatomy simply, clear cell lineage, well-defined genetics, and easily differentiated cell forms make it a powerful tool for studying the mechanisms of cell death including apoptosis, necrosis, autophagy, and ferroptosis. Here, we describe the understanding of micronutrient metabolism currently and also sort out the fundamental mechanisms of different kinds of cell death. A thorough understanding of these physiological processes not only builds a foundation for developing better treatments for various micronutrient disorders but also provides key insights into human health and aging.